A RETROSPECTIVE ANALYSIS ASSESSING THE FREQUENCY OF PATIENTS UNDERGOING GROWTH MODIFICATION WITH FUNCTIONAL APPLIANCES IN A UNIVERSITY SET UP - K, Monisha; Mary Varghese, Remmiya; Kumar , Aravind (International Journal of Psychosocial Rehabilitation, 2020)
Functional appliances are used worldwide and are most effective in the treatment of Class II Malocclusion. They are also used to achieve posterior extrusion to correct deep bites. The aim of the study was to assess the number of patients undergoing growth modification with different types of functional appliances and the age group which has the highest frequency of functional appliance usage. The study has been carried during a one-year period (June 2019 to April 2020) on 34 patients who used functional appliances. Data was collected from an electronic dental record consisting of all orthodontic diagnosis case sheets which were reviewed and preadolescents and adolescents in the age group between 8-17 years were chosen for the study. All relevant data obtained from the record system were exported to SPSS software and results were obtained using Chi square test. The findings of our study demonstrated that patients who had undergone Removable functional appliance therapy (69.70 %) were comparatively higher than the ones who had undergone treatment with fixed functional appliances (30.30 %). Majority of male patients had undergone removable functional appliance therapy. 42.42 % of patients were in the age group of 8-12 years (P value >0.05) Statistically not significant. The study concludes that the majority of the patients have undergone removable functional appliance therapy as compared to treatment with fixed functional appliances, but the study was not statistically significant. (P value >0.05).